Expression And Characterization Of Thermostable Lipase From Geobacillus thermodenitrificans IBRL- nra - Alsaedi, Alyaa Abdulhussein Kareem (2019)
In this study, the production of thermostable lipase by the G. thermodenitrificans IBRL-nra at 65°C was qualitatively determined by streaking the bacteria on Rhodamine B agar plate. Since lipases isolated from different sources exhibit diverse and umque characteristics, thermostable lipase from G. thermodenitrificans IBRL-nra was subjected for characterization to determine its properties.